2022
DOI: 10.2147/idr.s368792
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Epidemiological and Clinical Characteristics Between Invasive Candida Infection versus Colonization in Critically Ill Patients in a Tertiary Hospital in Anhui, China

Abstract: Objective Invasive infections due to Candida spp. have unique epidemiology, strain distribution, antimicrobial susceptibility, and clinical features. This study aimed to compare and evaluate these characteristic variables between invasive Candida infection and colonization of critically ill patients in local China to potentially improve differential diagnosis and therapy. Methods A total of 193 critically ill patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Some multi-center studies of Urumqi reported by Yi 22 and Abibai 23 found that the most common Candida species of invasive candidiasis were C. tropicalis and C. parapsilosis ,respectively. Similarly, a study conducted in a tertiary hospital in Anhui province and reported by Xia 24 identified C. glabrata as the most common isolates in invasive candidiasis. These findings indicated that the epidemiologic distribution of invasive Candida strains varied by region and time and was influenced by factors such as the source of the sample, the affected population, and the use of medications.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Some multi-center studies of Urumqi reported by Yi 22 and Abibai 23 found that the most common Candida species of invasive candidiasis were C. tropicalis and C. parapsilosis ,respectively. Similarly, a study conducted in a tertiary hospital in Anhui province and reported by Xia 24 identified C. glabrata as the most common isolates in invasive candidiasis. These findings indicated that the epidemiologic distribution of invasive Candida strains varied by region and time and was influenced by factors such as the source of the sample, the affected population, and the use of medications.…”
Section: Discussionmentioning
confidence: 78%
“…20,21 Within the scope of this study, C. albicans constituted the most frequently isolated pathogen, followed by C. glabrata, C. tropicalis, and C. krusei. Some multi-center studies of Urumqi reported by Yi 22 and Abibai 23 found that the most common Candida species of invasive candidiasis were 24 identified C. glabrata as the most common isolates in invasive candidiasis. These findings indicated that the epidemiologic distribution of invasive Candida strains varied by region and time and was influenced by factors such as the source of the sample, the affected population, and the use of medications.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, treating infections caused by NAC spp. can be challenging to physicians which could increase mortality rates especially among ICUs patients 27 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that critically ill hospitalized patients are at risk of developing systemic Candida infection with high morbidity and mortality, particularly immunocompromised and immunosenescent individuals (Qiao et al, 2023). Despite the lack of C. auris recovery from the oral cavity in our study, it is advocated that hospitals establish surveillance protocols that include testing of oral samples, in addition to the currently implemented screening for skin colonization.…”
Section: # Of Positive Cases/total Country Patient Gender Positive Mu...mentioning
confidence: 99%